Dugongs (Dugong dugon) along hyper-urbanized coastlines - Ng, Sirius Z. H.; Ow, Yan Xiang; Jaafar, Zeehan (Frontiers in Marine Science, 2022)
Coastal development and the increased anthropogenic use of sea spaces have rapidly degraded coastal habitats throughout Southeast Asia. We study how these activities impact dugong (Dugong dugon) population(s) along hyper-urbanized coastlines of the Johor and Singapore Straits through literature reviews and field surveys. Our review recovered sixty-nine live observations and carcass observations of dugongs between 1820 and 2021. The eastern Johor Strait is identified as a dugong hotspot. We observed peaks in observations coincident with the Northeast and Southwest monsoons. Distribution patterns of dugong observations were likely driven by a combination of natural and anthropogenic factors such as seasonality in seagrass abundance, tidal cycles, wind patterns and vessel traffic. Our field surveys ascertained active foraging sites along the anthropogenically disturbed Johor Strait and western Singapore Strait. Evident from our study is the importance of reef-associated seagrass meadows as refugia for foraging dugongs along areas of high anthropogenic use. This study provides an ecological baseline for dugong research along the Johor and Singapore Straits—within the data-poor western Malay Archipelago—, and aids in the design of sustainable management strategies and conservation programs for dugongs along areas where urbanization is commonplace.